Happiness in the Lab: What Can Be Learned about Subjective Well-Being from Experiments? - John Ifcher; Homa Zarghamee; Sandra H. Goff (Global Labor Organization (GLO), 2021)
The recent surge in analyses of subjective well-being (SWB) and the economics of happiness using large observational datasets has generated stylized facts about the relationship between SWB and various correlates. Because such studies are mostly concerned with the determinants of SWB, the modeling utilized assumes SWB to be the dependent variable. Often, selection effects, reverse causality, and omitted variable bias cannot adequately be controlled for, calling many of the stylized facts into question. This chapter explores the important contributions that happiness-in-the-lab experiments can make to the debates about stylized facts by testing the causality of the relationship between SWB and its correlates. A distinction is made between happiness-in-the-lab experiments in which SWB is a dependent versus independent variable, and methods for both types of experiments are discussed, along with a discussion of the limitations inherent in such experiments. The extant happiness-in-the-lab literature is reviewed and future directions for happiness-in the-lab research are proposed. The important role that happiness-inthe- lab experiments can play in the development of national SWB accounting is emphasized.
Keywords: C9; I31; 330; Subjective Well-Being; Happiness; Positive Affect; Randomized Controlled Trials (RCT); Economic Experiments & Causation